PENGARUH KELOMPOK REFERENSI DAN PROMOSI PENJUALAN TERHADAP MINAT BELI KONSUMEN PADA AZWA PERFUME PEKANBARU - Sintia Pratiwi; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Abstract The research conducted at AZWA Perfume Pekanbaruwhere located in Jl. Teuku Umar No. 79, Rintis, Lima Puluh. The problem in this study is number of buyers has decreasing, percentage of target achievement has decreased.This study aims to determine the effect of reference group and slaes promotion on consumer buying interest at AZWA Perfume Pekanbaru. In this study use quantitive descriptive with SPSS program. The population in this is are consumers at AZWA Perfume Pekanbaru. The sampling technique chosen is slovin Formula with a sample 100 respondents. Hypothesis testing uses a simple linear analysis method and multiple analysis with result showing that reference groupand sales promotionhave a positive and significant effect on consumer buying interestat AZWA Perfume Pekanbaru. With the calculation of the coefficient of determination (R2) reference groupon consumer buying interest the value of R square is 0,383 or 38,3% and sales promotionon consumer buying inerest the value of R square is 0,408 or 40,8% and coefficient of determination (R2) reference groupand sales promotion on consumer buying interest the value of R square is 0,480or 48,0%. This show that the reference groupand sales promotiongives an effect of 48% on consumer buying interestat AZWA Perfume Pekanbaru, while remaining 52%% is effected by other variables that are not examined in this study. Keyword: Reference Group, Sales Promotion And Consumer Buying Interest